Nutritional deficiencies and anemia in preschool children of Costa Rica, in 2014-2016 - Solano Barquero, Melissa (2018)
Objectives: (i) Determining the prevalence of nutritional deficiencies and anemia in preschool children who are beneficiaries from two nutritional aid programs (intramural and extramural) in the Education and Nutrition Centers and Children's Centers for Nutrition and Comprehensive Care (CEN-CINAI), and (ii) identifying the socioeconomic factors associated with nutritional deficiencies and anemia in these children. Methods: A total of 2503 children from 0 to 7 years old from 13 CEN-CINAI of the Central South Region of Costa Rica were surveyed in 2014-2016. Data on socioeconomic characteristics of their families were obtained using a structured questionnaire. In addition, anthropometric measurements (n = 2205) and blood samples for complete blood counts (n = 2203) were collected from the children. Results: We estimated a prevalence of nutritional deficiencies at 15.4% (95% confidence interval [CI]: 14.0-17.0) and anemia at 7.5% (95% CI: 6.4-8.6). Both conditions were more frequent in children aged ≤5 years (23.2% for nutritional deficiencies and 8.6% for anemia) and in beneficiaries from the extramural assistance program (41.9% and 10.6%, respectively). Other demographic and socio-economic factors, such as being female, living in inadequate housing with a roof made of natural material or waste, and being part of a large family (>4 members) were also associated with the presence of nutritional deficiencies and/or anemia. Conclusions: The prevalence of nutritional deficiencies and anemia observed in this study highlight the importance of intervening on modifiable socio-economic factors that influence these prevalences and improving the medical care of preschool children living in vulnerable conditions.